(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Colleges do everything to attract top students, providing quality academic programs in addition to residential and social facilities that make campus life more enjoyable. Every school canteen faces the same issue: not enough space to accommodate consumers during lunch or recess. Limited meal options. The terrible line at the canteen. When there are long lines, going to the canteen may appear to be a pleasure but is usually a chore. You need to create a welcoming and comfortable environment that tempts individuals to dine there during breaks. Canteens are where your students and employees will gather during breaks, so it is important to ensure that the spaces are welcoming and complement the school’s aesthetic. Most of the respondents are female, and also most of the respondents are from the 2nd-year level. The level of satisfaction of students in the school canteen was based on the canteen facilities, dining area, and ventilation. On the other hand, there are problems encountered by the respondents on limited dining space as well as limited choices of food, lack of canteen maintenance, unclean tables and chairs, and lack of trash bins. The researchers would like to recommend that the school canteen administration add more stalls for more food choices for the students. The researchers would like to recommend that the school canteen administration provide school canteen maintenance. The researchers would like to recommend that future researchers know the importance of research not only within the school but also in other aspects connected to the dining area.